Designing with the Body - Somaesthetic Interaction Design - Höök, Kristina (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2018)
With the rise of ubiquitous technology, data-driven design and the Internet of Things, our interactions and our interfaces with technology will look radically different in the years ahead, incorporating changes like full body interaction, shape-changing interfaces, wearables and movement tracking apps. These changes offer an enormous opportunityindeed, a necessity-to reinvent the way we interact with the inanimate world. Once-familiar, everyday objects, from our phones to our vacuums, require novel interaction models not just typing text on screens, but, increasingly, movementbased, bodily communication. A qualitative shift is required in our design methods, from a predominantly symbolic, language-oriented design stance, to an experiential, felt, aesthetic stance permeating the whole design and use cycle.